2018
DOI: 10.1002/mnfr.201800369
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Nondigestible Oligosaccharides Reduces Allergic Symptoms and Supports Low Dose Oral Immunotherapy in a Peanut Allergy Mouse Model

Abstract: scFOS/lcFOS and scFOS/lcFOS combined with low dose OIT are able to protect against a peanut-allergic anaphylactic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
3
12
1
Order By: Relevance
“…One of the most striking differences was that our data clearly indicates the role of SCFA in CMA, but not in PNA. Previously, we have shown that in PNA and CMA, increased levels of SCFA, specifically butyrate, coincided with allergy reduction [23,25]. These findings are confirmed in literature, where accumulating evidence indicates that SCFA have several anti-allergic properties by among others Treg induction and enhancement of the gut barrier function (as reviewed by [38]).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…One of the most striking differences was that our data clearly indicates the role of SCFA in CMA, but not in PNA. Previously, we have shown that in PNA and CMA, increased levels of SCFA, specifically butyrate, coincided with allergy reduction [23,25]. These findings are confirmed in literature, where accumulating evidence indicates that SCFA have several anti-allergic properties by among others Treg induction and enhancement of the gut barrier function (as reviewed by [38]).…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, in CMA, levels of fecal butyrate were increased in tolerant infants [41]. So even though we have observed that increased levels of SCFA coincided with an allergy reduction in both PNA and CMA using the dataset used in current analyses ( [23,25], we here show that the structure of how the experimental data are correlated with each other are different between the allergy models. This means that the relationship between the SCFA and the clinical outcomes in PNA a) is more indirect and/or b) occurs via different mechanisms or parameters which were not analyzed in the studies and/or c) is not essential for the outcome of the allergy, so the level of SCFA could be an epiphenomenon which is in contrast to the current opinion in literature as mentioned before.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The most frequently used adjuvants for the establishment of food allergy models are cholera toxin (CT, [17,44,45,46]), staphylococcus enterotoxin B (SEB, [47]), aluminium hydroxide (alum, [41,48,49]), and lipopolysaccharide (LPS, [50]).…”
Section: Usage Of Adjuvants In Food Allergy Mouse Modelsmentioning
confidence: 99%
“…Many of the published mouse food allergy models use cholera toxin to break oral tolerance towards co-applied allergens [16,40,45,46,51,55,56]. For example, Sun et al reported a mouse model in which C57BL/6 mice were sensitized against peanut protein by four times i.p.…”
Section: Usage Of Adjuvants In Food Allergy Mouse Modelsmentioning
confidence: 99%